NEPHROPROTECTIVE ACTIVITY OF BRIHATHYADI KASHAYAM IN ALBINO RATS (International Journal of Ayurveda and Pharma Research, 2020)
Brihathyadi kashayam mentioned in Yogarathnakara in the treatment of Mootrkrichra consists of combination of five simple drugs which are Brihathi, Prishnaparni, Kutaja, Paata, and Yasthimadhu. That is found to be more effective and safe in the treatment of Mutravahasrotovikaras. Aim and Objectives: Evaluation of Analytical study and the nephroprotective effect of Brihathyadi kashayam. Objectives: To prepare Brihathyadi kashayam according to classical reference, Experimental evaluation of Brihathyadi kashayam for its nephroprotective activity. Materials and Methods: Brihathyadi kashayam lower dose and higher dose were used in the study of nephroprotective activity in albino rats. The nephroprotective activity of Brihathyadi kashayam were evaluated against Rifampicin induced renal damage in albino rats. The results were analyzed by statistical methods. Results: In the experimental study the result was showed as the Brihathyadi Kashayam double dose was found effective in nephroprotective action, i.e., in reversing the degenerative changes caused in the nephrons by Rifampicin and lowering the serum creatinine, uric acid and urea levels comparing with the Brihathyadi Kashayam single dose and disease controlled group. Conclusion: This experimental study of Brihathyadi kashayam double dose showed the nephroprotective activity against the Rifampicin induced renal damage.